Combinatorial metabolic engineering of Escherichia coli for de novo production of structurally defined and homogeneous Amino oligosaccharides - Jinqi Shi; Chen Deng; Chunyue Zhang; Shu Quan; Liqiang Fan; Liming Zhao (Synthetic and Systems Biotechnology)
Amino oligosaccharides (AOs) possess various biological activities and are valuable in the pharmaceutical, food industries, and agriculture. However, the industrial manufacturing of AOs has not been realized yet, despite reports on physical, chemical, and biological approaches. In this study, the de novo production of chitin oligosaccharides (CHOS), a type of structurally defined AOs, was achieved in Escherichia coli through combinatorial pathway engineering. The most suitable glycosyltransferase for CHOS production was found to be NodCL from Mesorhizobium Loti. Then, by knocking out the nagB gene to block the flow of N-acetyl-d-glucosamine (NAG) to the glycolytic pathway in E. coli and adjusting the copy number of NodCL-coding gene, the CHOS yield was increased by 6.56 times. Subsequently, by introducing of UDP-N-acetylglucosamine (UDP-GlcNAc) salvage pathway for and optimizing fermentation conditions, the yield of CHOS reached 207.1 and 468.6 mg/L in shake-flask cultivation and a 5-L fed-batch bioreactor, respectively. Meanwhile, the concentration of UDP-GlcNAc was 91.0 mg/L, the highest level reported in E. coli so far. This study demonstrated, for the first time, the production of CHOS with distinct structures in plasmid-free E. coli, laying the groundwork for the biosynthesis of CHOS and providing a starting point for further engineering and commercial production.